Combustion Characteristics of A Wood Pellet Made of Albizia Chinensis and Rice Husk - Yuliati, Lilis; Hamidi, Nurkholis; Pragiwaka, Rafif Ezrha (International Journal of Mechanical Engineering Technologies and Applications, 2022)
To reduce dependence on fossil fuel, biomass, e.g. the wood pellet, has been developed in recent years.Â  Indonesia has an abundant source of biomass, e.g. wood and rice husk. This work investigates the combustion characteristics of the wood pellet made of Albizia Chinensis and rice husk. The analyzed combustion properties are ignition delay time, the mass of residue, combustion duration, combustion rate, maximum flame temperature, During the experiment, the rice husk content varies between 0 to 50%. As the rice husk content increases from 0 to 50%, the ignition delay time increases from 6 to 9.9 seconds, the mass of residue increases from 21.2 to 45 % and the combustion rate decreases from 0.55 to 0.52 g/min. In addition, higher rice husk content also decreases the maximum temperature.